If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -2y = 13forx Solving 5x + -2y = 13forx Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13forx' to each side of the equation. 5x + -13forx + -2y = 13forx + -13forx Reorder the terms: -13forx + 5x + -2y = 13forx + -13forx Combine like terms: 13forx + -13forx = 0 -13forx + 5x + -2y = 0 Add '2y' to each side of the equation. -13forx + 5x + -2y + 2y = 0 + 2y Combine like terms: -2y + 2y = 0 -13forx + 5x + 0 = 0 + 2y -13forx + 5x = 0 + 2y Remove the zero: -13forx + 5x = 2y Combine like terms: 2y + -2y = 0 -13forx + 5x + -2y = 0 The solution to this equation could not be determined.
| 6x+2y=47 | | (r^2)+4=-4r-19 | | 7x(3x/4) | | (4a-3)(2a+7)= | | 30w-(-w+6)+a(-5w+4)=-(5w+6)+(-8+3w) | | -6x+12+12-24=-36 | | 23x-14x+7=61 | | d=iqx | | y=3/2-1 | | 8x-3+6x=7x+5-9x | | .25x-35=50 | | 2x+2x+2=8x-14 | | 0=-2.5x+80 | | 21x+15-13x=-73 | | -n+8n=5n | | 9x+6x=195 | | 5(d+2)=3(d+-6) | | 2/5w | | 14+2x+6=24 | | 1.25x-6=x | | 9a-2=-3 | | 48n^3=147 | | 5x-4(4y-5x)+6y= | | 40=w^2+13w | | P=(20+.05x)+.15(20+.05x) | | 3X-5=X+53 | | 5.8x+9=33.64+3x | | 48n^3-147=0 | | 2x^2-14-3x=0 | | 7-3x+8x=-13 | | 6+2InX=5 | | 3(x-2)+8=2(x-3) |